Aesthetics and communication in video installations: the immersive space - Hernández, Iliana (Revista do Colóquio, 2022)
Through the concept of habitability, we seek to propose a form of relationship between the image-movement and the image-time, typical of Gilles Deleuze's thinking, and the conditions of experience proposed by video installations, through their devices, in which singular time is affected by the audiovisual, in its relationship with space, both external and internal to the works of art.